Transfusional iron overload in patients with sickle cell anemia: comparison between magnetic resonance imaging and serum ferritin - Bourbon Filho, Lécio dos Anjos (2011)
OBJECTIVE: To identify predictive variables of iron overload in patients with sickle cell anemia, correlating biochemical and imaging markers. MATERIALS AND METHODS: The authors developed a cross-sectional study involving 32 patients with sickle cell anemia who were evaluated for ferritin and iron serum levels and submitted to liver magnetic resonance imaging with one spin-echo and five gradient-echo sequences. The signal intensity was obtained at each sequence, corresponding to the arithmetical mean of the measurements on regions of interest in the liver and paraspinal muscles to obtain the liver/muscle signal intensity ratio (SIR). Based on such SIR, the liver iron concentration (LIC) was estimated by means of the following formula: e[5.808 - (0.877 × T2*) - (1.518 × IW)], where T2* is the SIR on the sequence with echo time = 13 ms and IW is the SIR on the intermediate-weighted sequence. Patients were grouped according to their blood transfusion regimen (regular monthly versus sporadic transfusions). RESULTS: The comparison between the transfusion groups was based on clinical-laboratory variables, with significant differences in SIR, LIC and serum ferritin levels: the group with regular transfusions demonstrated greater hepatic iron overload. CONCLUSION: Magnetic resonance imaging is an efficient tool for evaluating liver iron overload in patients with sickle cell anemia.